Bosnia and Herzegovina : Technical Assistance Report-Implementation of a New Reserve Requirement Framework. (IMF Staff Country Reports; Country Report ;, 2019)
Since 2014, the CBBH has been exposed to a negative spread on the reinvestment of the reserve requirements. Until 2014, the CBBH remunerated reserve requirements on the basis of the returns achieved on their reinvestment in the euro area money market. In 2014, when the European Central Bank (ECB) cut the deposit facility rate below zero, the CBBH decided not to follow the ECB in the remuneration of reserve requirements and to floor such remuneration to zero. Subsequently, in 2016, the CBBH decided to remunerate excess reserves at 50 percent of the ECB deposit facility rate and to continue remunerating reserve requirements at 0 percent. This exposes the CBBH to a negative spread of about 0.25 percent and 0.45 percent between the reinvestment yield and the remuneration of excess reserves and reserve requirements, respectively.